Low Temperature Thermoelectric Power of Ce(Pd1-x Cux)2Si2 - Encina, Sergio (2015)
We present the thermoelectric power S(T) of the Ce(Pd1−xCux)2Si2 alloy for temperatures 1.5K<T<300K. We observe three characteristic features across the 0<x<1 substitution range: two positive maxima and a negative minimum, that are typical for Ce compounds that display, or lie close to, magnetism. Our analysis of the data shows that the high-T maximum is related to the Kondo effect on excited crystal-field levels, but that the low-T one cannot be simply associated with the Kondo scale, TK. We speculate that disorder induced by alloying can be at the origin of this discrepancy and can also be responsible for the low S(T) measured at low temperatures in the 0.2<x<0.8 concentration range. We have extended electrical resistivity measurements on Ce(PdCu)Si2 (x=0.5) down to T∼40 mK in applied fields as high as 16 T.